Energy drink consumption among New Zealand adolescents: Associations with mental health, health risk behaviours and body size. (14th September 2017) - Utter, Jennifer; Denny, Simon; Teevale, Tasileta; Sheridan, Janie
Abstract : Aim: With the increase in popularity of energy drinks come multiple concerns about the associated health indicators of young people. The current study aims to describe the frequency of consumption of energy drinks in a nationally representative sample of adolescents and to explore the relationship between energy drink consumption and health risk behaviours, body size and mental health. Methods: Data were collected as part of Youth'12, a nationally representative survey of high school students in New Zealand (2012). In total, 8500 students answered a comprehensive questionnaire about their health and well‐being, including multiple measures of mental well‐being, and were weighed and measured for height. Results: More than one‐third (35%) of young people consumed energy drinks in the past week, and 12% consumed energy drinks four or more times in the past week. Energy drink consumption was significantly associated with greater depressive symptoms, greater emotional difficulties and lower general subjective well‐being. Frequent energy drink consumption was also associated with binge drinking, smoking, engagement in unsafe sex, violent behaviours, risky motor vehicle use and disordered eating behaviours. There was no association between consumption of energy drinks and student body size. Conclusions: Consumption of energy drinks is associated with a range of health risk behaviours for young people. Strategies to limit consumption of energy drinks by young people are warranted.